Reversible mono-ADP-ribosylation of DNA breaks. - Munnur, D; Ahel, I (Wiley, 2017)
ADP-ribosylation is a chemical modification of macromolecules that plays an important role in regulation of quintessential biological processes such as DNA repair, transcription, chromatin remodelling, stress response, apoptosis, bacterial metabolism and many others. ADP-ribosylation is carried out by ADP-ribosyltransferase proteins, such as poly(ADP-ribose) polymerases (PARPs) that transfer either monomer or polymers of ADP-ribose onto the molecular targets by using nicotinamide adenine dinucleotide (NAD(+) ) as a cofactor. Traditionally, proteins have been described as primary targets of ADP-ribosylation; however, there has been growing evidence that DNA may be a common target as well. Here, we show using biochemical studies that PARP3, a DNA damage activated ADP-ribosyltransferase, can mono ADP-ribosylate double stranded DNA ends. ADP-ribosylation of DNA mediated by PARP3 attaches a single mono-ADP-ribose moiety to the phosphate group at the terminal ends of DNA. We further show that mono ADP-ribosylation at DNA ends can be efficiently reversed by several cellular hydrolases (PARG, MACROD2, TARG1 and ARH3). This suggests that mono ADP-ribosylated DNA adducts can be efficiently removed in cells by several mechanisms. This article is protected by copyright. All rights reserved.